CNT-reinforced adhesive joint between grit-blasted steel substrates fabricated by simple resin pre-coating method. Issue 7 (7th June 2018) - Wang, Binhua; Hu, Xiaozhi; Hui, Jizhuang; Lu, Pengmin; Jiang, Bin
ABSTRACT: A simple method of applying and distributing multi-walled carbon nanotubes (MWCNTs) onto grit-blasted steel substrates has been investigated in this study to overcome the difficulty of mixing MWCNTs in epoxy adhesives forming the MWCNT-reinforced adhesive joints. MWCNTs were dispersed in an acetone and resin (no hardener) solution with the weight ratio of 1:3:100 for MWCNT/resin/acetone, which was then applied onto the grit-blasted steel substrates. After evaporation of acetone, an ultra-thin layer of resin pre-coating kept well-distributed MWCNTs within the micro-cavities created by grit blasting. Epoxy adhesives (with hardener) were then applied to bond the steel substrates to create MWCNTs-reinforced adhesive joints. The results show that the MWCNT pre-coating (PC) method is beneficial to strong adhesive bonding. Most importantly, the MWCNT-PC method can be easily applied for structural applications on site. In the current study, MWCNTs were simply dispersed in the acetone and resin (no hardener) solution by simple rod stirring for around 1 minute, which can be adopted for large-scale applications. Scanning electron microscopy (SEM) observations on fracture surfaces and cross sections of the MWCNT-reinforced adhesive joints showed MWCNT micro-bundles were well dispersed within the epoxy adhesive joints taking the contour of microscopically uneven substrate surfaces.